Comprehensive study on effect of sintering temperature on the physical, structural and optical properties of Er3+ doped ZnO-GSLS glasses - Abdul Rashid, Siti Syuhaida; Ab Aziz, Sidek; Matori, Khamirul Amin; Mohd Zaid, Mohd Hafiz; Mohamed, Nurzilla (Elsevier, 2017)
The Er3+ doped zinc soda lime silica (ZnO-GSLS) glass system was prepared by the conventional melt-quenching technique using waste green soda lime silica (GSLS) glass, zinc oxide (ZnO) and erbium oxide (Er2O3) powder as starting materials. Er3+ doped willemite based glass-ceramics (Zn2SiO4:Er3+) were derived from this precursor glass by a controlled sintering process. The effect of sintering temperature on the density and linear shrinkage of the sample was investigated. XRD analysis revealed the presence of thermodynamically stable zinc orthosilicate (α-Zn2SiO4) phase at sintering temperatures above 700 °C. FESEM image shows the presence of densely packed grains as the sintering temperature increase. FTIR spectroscopy was used to observe the structural of SiO4 and ZnO4 groups in the formation of willemite phase evolution. The UV–Vis absorption spectra reveals four peaks centered at excitation of electron from ground state 4I15/2 to 4G11/2 (∼363 nm), 4F7/2 (∼488 nm), 2H11/2 (∼523 nm), and 4F9/2 (∼652 nm). PL spectroscopy measurements were performed at room temperature using 385 nm excitation wavelengths. Enhancement of the Er3+ luminescence was observed with the progression of sintering temperature.